Pop, Luka, dan Tekanan untuk Pulih: Maskulinitas dan Emosi dalam Budaya Kawula Muda Indonesia - Naim, Chanif Ainun (Kinesik, 2025)
Focusing on the works of Tulus, Hindia, and Kunto Aji, this study explores how themes of anxiety, healing, and self-reflection are articulated through the intertwined logics of late capitalism and metamodern sensibility. Employing perspectives from affect theory, gender studies, and political economy, the analysis reveals that these emotional narratives, while intimate and seemingly subversive, often reproduce neoliberal norms by transforming vulnerability into a consumable aesthetic. The emergence of “affective masculinity” complicates dominant gender expectations by embracing softness and introspection, yet it remains entangled in capitalist modes of emotional labor. Ultimately, Indonesian pop music becomes a site where sincerity and commodification, rebellion and resignation, continuously oscillate. This article argues for deeper critical engagement with how affective expression in youth culture both reflects and regulates emotional life under capitalism.